1960
DOI: 10.1071/ph600625
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic Micropulsations

Abstract: SummaryThis paper describes simultaneous observations of geomagnetic micropulsations at three places ranging from 28 0 S. to 51 0 S. geomagnetic latitude. It is shown that there is no observable change in the micropulsation period with latitude although there is a monotonic increase in the amplitude with latitude for all periods between 10 and 100 sec. The interpretation of these results in terms of existing theories is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1

Year Published

1961
1961
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 4 publications
2
9
1
Order By: Relevance
“…However, we believe that this oscillation is possible when these periods of oscillations become equal at finite interval of latitudes. This supposition is in agreement with the observations of Ellis (1960), Kokubun and Nagata (1965), Obertz and Raspopov (1968), who have shown that geomagnetic pulsations observed simultaneously at different latitudes have the equal period and a similar spectrum. The component changes its sign when crossing the longitude of the source of oscillations.…”
supporting
confidence: 81%
“…However, we believe that this oscillation is possible when these periods of oscillations become equal at finite interval of latitudes. This supposition is in agreement with the observations of Ellis (1960), Kokubun and Nagata (1965), Obertz and Raspopov (1968), who have shown that geomagnetic pulsations observed simultaneously at different latitudes have the equal period and a similar spectrum. The component changes its sign when crossing the longitude of the source of oscillations.…”
supporting
confidence: 81%
“…That is, the pulsations at lower latitude stations were abundant in the vicinity of 180 sec while at higher latitudes the pulsations with period nearly 270 sec occurred more frequently. In some earlier investigations no change in the period of Pc5 with increasing latitude was detected (ELLIS, 1960;KOKUBUN and NAGATA, 1965;OBERTZ and RASPOPOv, 1968) but some other authors reported an increase of the period with increasing latitude (OBAYASHI and JAcoBS, 1958;OGUTI,1963;OL',1963;HIRASAWA,1970;GUPTA, 1974a). For pulsations in the period range 180-300 sec the period-latitude profile, obtained from the whole body of data at individual stations, is shown in Fig.…”
Section: Periodmentioning
confidence: 99%
“…The statistical behavior of ground Pc4 pulsations is well documented, including an amplitude maximum on the dayside and lack of events on the nightside [ Saito , 1964; Fukunishi and Lanzerotti , 1974; Chi et al , 1994, 1996]. The Pc4 amplitude peaks at magnetic latitudes below ∼60° [ Samson and Rostoker , 1972], and at low latitudes the amplitude is typically 0.5 nT [ Ellis , 1960]. Possible sources of the pulsations are ULF waves generated by ion‐beam instability in the solar wind upstream of the bow shock [ Troitskaya et al , 1971] and the Kelvin‐Helmholtz instability on the magnetopause [ Greenstadt et al , 1979].…”
Section: Introductionmentioning
confidence: 99%